Analisis Ketepatan Model Prediksi Financial Distress pada Perusahaan Sektor Properti dan Real Estate - Resi Anjarwati; Siti Resmi (Akademi Akuntansi YKPN Yogyakarta, 2023)
The study aims to analyze differences in the accuracy of the financial distress prediction model using Altman Z-Score , Zmijewski, Springate, and Grover for property and real estate sector companies listed on the Indonesia Stock Exchange in 2021. The sampling method uses non- probability sampling with a purposive sampling method. The number of samples used in this study were 63 companes. The data analysis method used is to test the accuracy of the prediction model and the chi square test. The result of this study indicated that there are differences in the accuracy of financial distress predictions using four models, Altman Z-Score, Zmijewski, Springate, and Grover for property and real estate sector companies listed on the Indonesia Stock Exchange.